A theoretical model to analyze the Central to Eastern Pacific El Niño continuum. (October 2018) - Morel, Yves; Thual, Sulian; Delcroix, Thierry; Hall, Nick; Alory, Gaël
Highlights: We derive analytical solutions for the propagation of Equatorial Kelvin waves in a varying background. It is used to understand the mechanisms leading to Central or Eastern Pacific El Nino events. Central Pacific events require the existence of a frontal structure of the mixed layer. Diabatic effects can be included in the model and have significant impact on the signature of the wave. Multiple waves can lead to a transition from Central to Eastern Pacific structures. Abstract: A current scientific issue of great interest is to understand the mechanisms leading to the localization of El Niño events either in the Central (CP) or Eastern Pacific (EP). For this, we derive a reduced gravity mixed layer model for the equatorial ocean with simple nonlinearities, diabatic effects and zonally varying background characteristics. Using the model, we study the propagation of an equatorial Kelvin wave from an initial perturbation. An approximate analytical solution is found for the evolution of the maximum density (or temperature) anomaly created during the passage of the wave. Density anomalies can either peak in the CP or continuously increase until reaching the EP, which is representative of both types of El Niño. Sensitivity tests reveal that both the zonally varying background stratification and diabatic effects are important to determine the density pattern. The EP pattern is obtained for smooth background variations while the CP pattern requires a frontal background structure. Using numerical experiments, we then show how consecutive Kelvin waves can lead to the transition from a CP to an EP pattern. The present theoretical results provide useful insights for understanding El Niño dynamics and diversity in more complete models and observations.